2018
DOI: 10.1016/j.chemosphere.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic biotransformation of the antibiotic ciprofloxacin by Bradyrhizobium sp. isolated from activated sludge

Abstract: Ciprofloxacin (CIP) is an antibiotic that is widely used to treat bacterial infections and is poorly biodegraded during wastewater treatment. In this study, a CIP-degrading bacterial strain (GLC_01) was successfully retrieved from activated sludge by enrichment and isolation. The obtained bacterial strain shares over 99% nucleotide identity of the 16S rRNA gene with Bradyrhizobium spp. Results show that Bradyrhizobium sp. GLC_01 degraded CIP via cometabolism with another carbon substrate following a first-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 43 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…The widespread use of CIP leads to its occurrence at relatively high concentration than others in its group. (Nguyen et al, 2018). As expected based on previous work (Larsson et al, 2007;Nguyen et al, 2017;Tran et al, 2018), Secondary effluent, hospital wastewater and pharmaceutical wastewater have been found with CIP at concentration of 10 -200 µg/L and 6.5 -31 mg/L.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The widespread use of CIP leads to its occurrence at relatively high concentration than others in its group. (Nguyen et al, 2018). As expected based on previous work (Larsson et al, 2007;Nguyen et al, 2017;Tran et al, 2018), Secondary effluent, hospital wastewater and pharmaceutical wastewater have been found with CIP at concentration of 10 -200 µg/L and 6.5 -31 mg/L.…”
Section: Introductionsupporting
confidence: 84%
“…Another six reactors were exposed to 50 and 500 µg/L of CIP for two months. The exposure concentrations were environmentally relevant levels in wastewater (Nguyen et al, 2018).…”
Section: Cip Exposure In As Bioreactormentioning
confidence: 99%
“…For instance, Terzic et al (2018) observed an increase from none to 99% removal of antibiotic macrolide after two months of exposure. Likewise, Nguyen et al (2018) retrieved a Bradyrhizobium sp. from AS via an enrichment and isolation process, which showed the ability to cometabolite antibiotic ciprofloxacin.…”
Section: Removal Routes For Dcf In Activated Sludgementioning
confidence: 99%
“…For some antibiotics of sulfonamides class (e.g., SMX and SDZ) and trimethoprim (TMP), sorption onto biological sludge plays a minor role in their removal in engineered biological treatment systems, , and therefore, biodegradation is the principal pathway for their removal. Biodegradation is a process that involves the breakdown of complex organic compounds including antibiotics either through biotransformation, resulting in formation of different metabolic intermediates (i.e., dead end and/or transitory intermediates) or through complete mineralization to CO 2 and H 2 O ,, by pure or mixed microbial culture. The terms biotransformation and biodegradation are interchangeably used in the literature.…”
Section: Removal Pathways Of Antibiotics In Engineered Biological Sys...mentioning
confidence: 99%
“…Different intermediates could be formed either by breakdown of the parent antibiotic compounds ,,, or by hydroxylation, acetylation of the amino group in SMX, , and loss of N -methyl group by demethylation of the dimethyl amino group at C4 position of TET molecule without breakdown of the parent compound. Microorganisms have the ability to degrade antibiotics utilizing them as a sole carbon and energy source and/or via cometabolism. ,, Several recent studies focused on possible biodegradation mechanisms (including intermediates, pathways, functional microorganisms, catabolic enzymes, and genes) of antibiotics in different microbial sludge systems, which are important to elucidate the fate of antibiotics in the environment. , The following section examines the biodegradation mechanisms of the selected target classes of antibiotics. Moreover, the biotransformation and mineralization by pure and mixed cultures under different redox conditions, intermediates, pathways, catabolic enzymes, and genes involved are also discussed.…”
Section: Removal Pathways Of Antibiotics In Engineered Biological Sys...mentioning
confidence: 99%